The language of sedation in end-of-life care: The ethical reasoning of care providers in three countries. (July 2015) - Seale, Clive; Raus, Kasper; Bruinsma, Sophie; van der Heide, Agnes; Sterckx, Sigrid; Mortier, Freddy; Payne, Sheila; Mathers, Nigel; Rietjens, Judith; ,
The application of ethically controversial medical procedures may differ from one place to another. Drawing on a keyword and text-mining analysis of 156 interviews with doctors and nurses involved in end-of-life care ('care providers'), differences between countries in care providers' ethical rationales for the use of sedation are reported. In the United Kingdom, an emphasis on titrating doses proportionately against symptoms is more likely, maintaining consciousness where possible. The potential harms of sedation are perceived to be the potential hastening of social as well as biological death. In Belgium and the Netherlands, although there is concern to distinguish the practice from euthanasia, rapid inducement of deep unconsciousness is more acceptable to care providers. This is often perceived to be a proportionate response to unbearable suffering in a context where there is also greater pressure to hasten dying from relatives and others. This means that sedation is more likely to be organised like euthanasia, as the end 'moment' is reached, and family farewells are organised before the patient is made unconscious for ever. Medical and nursing practices are partly responses to factors outside the place of care, such as legislation and public sentiment. Dutch guidelines for sedation largely tally with the practices prevalent in the Netherlands and Belgium, in contrast with those produced by the more international European Association for Palliative Care whose authors describe an ethical framework closer to that reportedly used by UK care providers.